Subsea pipeline integrity and risk management - Bai, Yong (Gulf Professional Publishing, 2014)
Subsea repairs and inspection are costly for petroleum and pipeline engineers and proper training is needed to focus on ensuring system strength and integrity. Subsea Pipeline Integrity and Risk Management is the perfect companion for new engineers who need to be aware of the state-of-the-art techniques. This handbook offers a ""hands-on"" problem-solving approach to integrity management, leak detection, and reliability applications such as risk analysis. Wide-ranging and easy-to-use, the book is packed with data tables, illustrations, and calculations, with a focus on pipeli
Includes bibliographical references and index
Keywords: Offshore oil well drilling / Safety measures; Offshore structures / Design and construction; Underwater pipelines / Corrosion; Underwater pipelines / Design and construction; Underwater pipelines -- Corrosion; Underwater pipelines -- Design and construction; Offshore structures -- Design and construction; Offshore oil well drilling -- Safety measures; Offshore oil industry -- Risk management